Geometrical theory of diffraction for electromagnetic waves - James, Graeme L. 1945- (Institution of Engineering and Technology, 1986)
The book dealt with the following topics: electromagnetic fields; canonical problems for GTD; geometrical optics; diffraction by straight edges and surfaces; diffraction by curved edges and surfaces; application to some radiation and scattering problems.